Sistem Informasi Pelayanan Kamar Asrama LPMP Sumatera Barat Berbasis Web - Adri Yanto (Pusat Riset dan Inovasi Nasional, 2024)
The Dormitory Room Data processing system at LPMP West Sumatra still uses the method of filling in data with a piece of paper for reception of guests at LPMP West Sumatra and there is no automatic processing using a particular system, therefore the author conducted research at the Education Quality Assurance Institute in Sumatra Province West by collecting information and data that will be processed to create an information system for the West Sumatra LPMP Dormitory Room Service which consists of data input, data processing and report preparation. This information system can produce Guest Data Recap reports, Financial Data Recap reports, Room Availability Data Reports and Guest Order Data recap reports. This information system was designed and adapted to the needs of the West Sumatra Province Education Quality Assurance Institute (LPMP) to make it more effective and efficient, and it is hoped that the West Sumatra LPMP Dormitory Room Service Data processing can be optimized.